CURTAIN PURCHASE AGREEMENT IN ACCORDANCE WITH THE BA'I ISTISHNA CONTRACT AT THE GORDEN REKA STORE, BANDA ACEH - INDONESIA - Munandar, Ari; Yuhasnibar (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2024)
The very diverse needs of the community have given rise to various innovations in products, product design and quality. Some people tend to need and are interested in unique products that do not have an equivalent in the market, so they need certain parties who are able to meet the products that consumers need. One of the products that consumers need is curtains. This product is widely ordered during Eid and in the office, one of the stores that provides this service is the Reka Curtain Shop located in Pasar Aceh. The purpose of this study is to find out how the practice in the procurement of curtains is carried out by the Reka Curtain Shop, and how the responsibility of the Reka Curtain store management to the provisions of the time for the delivery of curtain products. The method of this research uses a type of empirical juridical research, namely problem solving by collecting, processing, analyzing data and drawing conclusions systematically and objectively. The result of this study is that all consumer orders can be submitted on time and in accordance with consumer wishes, except for certain conditions caused by force majeure factors and also other natural factors that hinder the process of manufacturing even though in a small degree of professionalism is lacking.